Genome sequence of Sphingomonas sp. S17, isolated from an Alkaline, hyperarsenic, and hypersaline volcano-associated lake at high altitude in the Argentinean Puna - Farias, M.E. (2011)
The high-altitude Andean lakes (HAAL) in the Argentinean Puna-high Andes region represent an almost unexplored ecosystem exposed to extreme conditions (high UV irradiation, hypersalinity, drastic temperature changes, desiccation, and high pH). Here we present the first genome sequence, a Sphingomonas sp., isolated from this extreme environment. © 2011, American Society for Microbiology.